2001
DOI: 10.1097/00002030-200109070-00004
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cell surface CCR5 density as a host factor in HIV-1 disease progression

Abstract: These results are compatible with the hypothesis that CCR5 density, which is a key factor of HIV-1 infectability, determines in-vivo HIV production, and thereby the rate of CD4 cell decline. Consequently, CCR5 density quantitation could be a new valuable prognostic tool in HIV-1 infection. Moreover, these data emphasize the therapeutic potential of treatments that reduce functional CCR5 density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
78
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 16 publications
8
78
2
Order By: Relevance
“…HIV-1 viral strains preferentially use a number of chemokine receptors including CXCR4, CCR2, 3, and 5 as coreceptors for viral entry into lymphocytes and macrophages (11,84). It has recently been shown that the level of chemokine receptor expression may predict susceptibility to the development of AIDS (14,16,85). Rheumatoid arthritis is another disease that preferentially affects the elderly (86 -88).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 viral strains preferentially use a number of chemokine receptors including CXCR4, CCR2, 3, and 5 as coreceptors for viral entry into lymphocytes and macrophages (11,84). It has recently been shown that the level of chemokine receptor expression may predict susceptibility to the development of AIDS (14,16,85). Rheumatoid arthritis is another disease that preferentially affects the elderly (86 -88).…”
Section: Discussionmentioning
confidence: 99%
“…ϩ T cells is a marker of disease progression (39). Collectively, these findings raise the concern that, beyond a series of obvious similarities, the SIVmac-infected RM model does not reproduce correctly the pathogenic events occurring during HIV infection, particularly with respect to the dynamics of the CD4 ϩ CCR5 ϩ T-cell subset.…”
Section: Ccr5mentioning
confidence: 96%
“…Interestingly, the correlation between CCR5 expression and viremia is logarithmic, a small difference in CCR5 density resulting in a marked difference in HIV RNA plasma levels. As a consequence, we have also established that in infected persons CCR5 cell surface density correlates with disease progression (6). The aim of the present study was to analyze the molecular mechanisms responsible for this correlation.…”
mentioning
confidence: 87%